2013
DOI: 10.1111/eje.12065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the students' perspectives of a clinic mentoring programme

Abstract: The purpose of this article is to describe and examine the effectiveness of a mentoring program for third and fourth year clinical dental students. This is an educational intervention for the pre-doctoral students at the Schulich School of Dentistry. We have recently instituted this program and have developed a questionnaire to assess the student perspectives using a SWOT analysis of the strengths, weaknesses, opportunities and threats of this intervention by analyzing the quantitative and qualitative response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In order to reduce students’ stress and to increase their self-confidence, several universities that run training programs centered on NTS acquisition have stressed the importance of conducting this training alongside clinical practice [ 10 , 25 , 30 , 33 ]. However, some of these studies focused on one specific NTS, the most common being communication [ 10 , 11 , 30 ], followed by teamwork [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce students’ stress and to increase their self-confidence, several universities that run training programs centered on NTS acquisition have stressed the importance of conducting this training alongside clinical practice [ 10 , 25 , 30 , 33 ]. However, some of these studies focused on one specific NTS, the most common being communication [ 10 , 11 , 30 ], followed by teamwork [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Holmes et al also reported that students could be productive in a comprehensive patient care environment and achieve competence without numerical requirements 8 . The benefits of faculty mentorship in patient management skills have been found to be valuable in a successful comprehensive care patient delivery system 9 . Our study sought to contribute to this development of knowledge about the value of a comprehensive care model in clinical education.…”
mentioning
confidence: 88%
“…Feelings of preparedness are important in the successful transition from being a student to a practicing dentist 6 . To transit from the preclinical to clinical year successfully, dental students must develop self‐confidence in their abilities 7 . However, there is a lack of research regarding the most beneficial type of intern training pattern in terms of developing confidence in the last year of dental school in Mainland China and the advantages and disadvantages of the two types of intern patterns.…”
Section: Main Differences Between One‐stage Pattern and Three‐stage Pmentioning
confidence: 99%